2017
DOI: 10.1155/2017/1614654
|View full text |Cite|
|
Sign up to set email alerts
|

Determination of Metals Present in Textile Dyes Using Laser-Induced Breakdown Spectroscopy and Cross-Validation Using Inductively Coupled Plasma/Atomic Emission Spectroscopy

Abstract: Laser-induced breakdown spectroscopy (LIBS) was used for the quantitative analysis of elements present in textile dyes at ambient pressure via the fundamental mode (1064 nm) of a Nd:YAG pulsed laser. Three samples were collected for this purpose. Spectra of textile dyes were acquired using an HR spectrometer (LIBS2000+, Ocean Optics, Inc.) having an optical resolution of 0.06 nm in the spectral range of 200 to 720 nm. Toxic metals like Cr, Cu, Fe, Ni, and Zn along with other elements like Al, Mg, Ca, and Na we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…In this approach, the strongest lines of all the elements were chosen and the integrated peak intensities of the selected lines were utilized to estimate the relative abundances of the elements in the sample [22]. In particular, all of the above-mentioned emission lines of the detected elements were utilized in this analysis.…”
Section: Weight Percentage Methodmentioning
confidence: 99%
“…In this approach, the strongest lines of all the elements were chosen and the integrated peak intensities of the selected lines were utilized to estimate the relative abundances of the elements in the sample [22]. In particular, all of the above-mentioned emission lines of the detected elements were utilized in this analysis.…”
Section: Weight Percentage Methodmentioning
confidence: 99%
“…The chosen analytical procedure in the current work, LIBS, is basically an atomic emission spectroscopic technique, which has been proven to be quite reliable to reveal the chemical composition of the samples in solid liquid and gaseous phases (Hussain and Gondal, 2008;Gondal et al, 2009;Rehan et al, 2018d). When the high energy pulse of laser beam hits the sample surface, the generations of intense plasma take place through target heating, melting, and change of phase, ionization and excitation (Ali et al, 2016;Rehan et al, 2016Rehan et al, , 2017Rehan et al, , 2018b. LIBS method of detection is quite sensitive, rapid and does not require any sample preparation and hence a minute level of elements exist in the sample can easily be detected.…”
Section: Introductionmentioning
confidence: 99%
“…The use of laser optical instruments is more accurate and is safer than x-rays [2,3]. In general, laser spectroscopy method has many advantages, comparing to x-ray spectroscopy [4].…”
Section: Introductionmentioning
confidence: 99%
“…Authors in [3] present the results of laser spectroscopy usage for detection of metals in textile dyes. The results of the study revealed the presence of such toxic metals as Cr, Cu, Fe, Ni, and Zn.…”
Section: Introductionmentioning
confidence: 99%